Developing Vocational Training: Lesson Learnt from Building Business Model Innovation Through Customer Experience and Distinctive Organizational Capability - Mihardjo, Leonardus; Elidjen; Alamsjah, Firdaus; Sasmoko (Journal of Technical Education and Training, 2020)
A vocational training can be invested based on the degree of innovation, such as on business models to face challenges in the era of Industrial Revolution 4.0. The lesson learnt can be captured through the formulation of strategy that needed to consider internal and external aspects. For example, as in the digital world, customer experience as well as customer satisfaction. Capability on the side of the network owned combined with network and social capabilities are expected to create distinctive organizational capability. Based on this background, the study aims to examine the effects of customer experience and distinctive organizational capability on the business model innovations of telecommunication firms in Indonesia using quantitative research. The target population are 445 telecommunication network companies in Indonesia which includes 312 ISP firms, 34 satellite firms, 27 tower firms, and 72 Telkom subsidiaries and affiliates, with samples taken from 34 firms. PLS is used as the analytical tool to process the data in this study. The results of the study show that customer experience and distinctive organizational capabilities have an influence to business model innovations. Customer experience has a bigger role than distinctive organizational capability in building business model innovation. These findings have practical implications for the management of telecommunications industries in Indonesia as the development of vocational training rely on the needs of business model innovation development, which directly based on the development of customer experience and supported with development of distinctive organizational capability. Further research can be explored by expanding the sample, industry and in other countries.